The relationship between parental anxiety, child’s behavioral inhibition and child anxiety - Azham, Adlina Aisya; Janon, Nazariah Sharie (Southeast Asia Early Childhood Journal, 2021)
The purpose of this cross-sectional study was to investigate the role of a child’s behavioral inhibition in mediating the relationship between parental anxiety and childhood anxiety in the Malaysian context. Participants were 92 parents (father = 23, mother = 69) of young children aged four to six years old. They completed three measures which were The Beck Anxiety Inventory (BAI), The Preschool Anxiety Scale (PAS) and Behavioral Inhibition Questionnaire (BIQ). Results indicated that there was a correlation between; (i) parental anxiety and child anxiety; and (ii) child’s behavioral inhibition and child anxiety, which supported our hypothesis. However, our findings did not provide support for the hypothesis that a child’s behavioral inhibition plays a mediating role in the association between parental anxiety and childhood anxiety. Although this study does not illuminate the mediating role of a child’s behavioral inhibition, our results still provided a groundwork for the development of a specific early intervention program for young children in Malaysia with childhood anxiety symptoms, with the inclusion of precursors of the presence of parental anxiety and child’s behavioral inhibition. Future improvements should focus on recruiting a larger sample size and incorporating the feedback from both father and mother in completing the measures.